Kajian Pustaka: Kadar Brain Derived Neurotrophic Factor Mempengaruhi Berat Badan Lahir pada Bayi - Yessi Ardiani; Defrin Defrin; Husna Yetti (Universitas Batanghari Jambi, 2019)
Brain Derived Neurotrhophic Factor (BDNF) is one of the proteins needed for the growth of neurons. During its development period BDNF plays a role in nerve growth, differentiation, repair, and survival of nerve cells. In addition, researchers from certain groups found that BDNF also had an important role during the implantation period, placental development and development of fetal growth. BDNF is known to have an important role in regulating angiogenesis needed for placental development. Because of this role, BDNF deficiency will cause disruption in placental growth which will eventually cause fetal growth disorders or Intrauterine growth restriction (IUGR). In recent years studies have shown that neurotrophins play an important role in the regulation of placental development and fetal growth. BDNF has been found to be expressed in large amounts in blastocysts which indicate the potential role of BDNF in implantation and development of the placenta. BDNF is also produced in the muscle tissue of one of them in the uterus precisely in the endometrium and myometrium. The discovery of the role of BDNF, is expected to be used as an indicator to assess the occurrence of growth disorders in the fetus as well as additional information about the etiology and pathophysiology of IUGR. Keywords: BDNF; IUGR; Neurotrophin